What an IP address can reveal about you: a report prepared by the Technology Analysis Branch of the Office of the Privacy Commissioner of Canada. - Privacy Commissioner of Canada; Canadian Electronic Library (Office of the Privacy Commissioner of Canada, 2013)
"Over the past decade, the Government of Canada has tabled various iterations of so called lawful access legislation. The latest one identified six specific elements of subscriber information which would be made available to law enforcement and national security authorities without prior judicial authorization ... This document presents findings from a technical analysis conducted by the Office of the Privacy Commissioner of Canada (OPC) examining the privacy implications of subscriber information elements which are not found in a phone book: email address, mobile phone number and Internet Protocol (or IP) address"–Introduction.